Effect of oxygen potential and fluxing components on phase relations during sintering of iron ore - Mcbow I.; Kongoli F.; Budd R.; Llubani S.; Yazawa A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The optimal operation of the blast furnace depends considerably on the properties of the sinter fed into the furnace. As a result, the optimization of the sintering processes has a direct effect on the overall effectiveness of the iron making processes. In order to produce a good sinter special care needs to be taken in order to assure it has a good permeability and reducibility and it is able to retain these properties for a certain time. If the sinter starts to melt down early in the upper part of the blast furnace, where its solid state reduction is essential, permeability decreases, the gas channels get blocked, reductibility diminishes and serious problems may also follow. Among the factors that influences the above mentioned sinter properties are the oxygen potential and fluxing components. Nevertheless, their effect on the phase relations during sintering and sinter reduction conditions has not yet entirely clarified and confusion exists in literature. This quantification becomes even more important today where many new minor components such as Al2O3 and MgO enter the sinter through raw materials. This work quantifies the effect of oxygen potential and fluxing components such as alumina and magnesia on the liquidus and phase relations of the sinter primary melts in the iron rich portion of CaO-FeO-Fe2O3-SiO2 system at sintering conditions. This is carried out by the means of new type of industrial diagrams in the form of Fe/CaO vs. SiO2 that can directly help the optimization of the sintering processes.